The discipline of data visualization in 2017 - Pérez-Montoro, Mario (Anuario ThinkEPI, 2018)
Recent advances in technology have provoked changes in the information visualization discipline. This article reviews some innovative visualizations and organizes them into three groups. First, we present a small selection of visualizations that incorporate conceptual novelties and new visual proposals. Second, we show some other ones that have drawn attention to the importance of the data set they have visualized. Finally, we account for some of the technological advances that were made in 2017 within the discipline.
Keywords: Data visualization; 2017; Trends; Information visualization; Interactive visualization; Infographics; Multimedia visualization; Concepts; Contents; Technology.